Monodevelopment of Specialized Social Nodes in the Structure of the Newest Space in the Region - Смочко, Наталія Михайлівна; Лужанська, Тетяна Юріївна (Київський національний університет імені Тараса Шевченка, 2021)
The purpose of this work is to study specialized social nodes as the dominants of social space and the result of the orientation of socio-geographical processes to places of social power, their "point" expression in the newest space of the region. Methods. The study used general scientific methods, including analysis, scientific synthesis, analytical method, methods of comparison and generalization. Scientific novelty. The article reveals great attention is paid to specialized social nodes that are dominant in the social space. The genesis of the first social nodes as religious centres for marking holy places in space, the search for the "centre of the world" at a specific hierarchical level of the territorial system, the ordering of socio-geographical relations and vision of the world more stable. The definition of "specialized social nodes" is interpreted as mono-nodes formed by a specific type of social infrastructure, which provides one type of socialization or performs one infrastructure service, providing one or another type of socialization. It has been proved that social space can be considered at the most generalized level as a social monospace at the angle of considering the process of socialization as a generating feature. Specialized educational nodes as dominants in the specialized educational social mono-space, generalized at the national level, which is formed by all educational institutions of Ukraine, are outlined. The definition of "specialized social educational nodes or educational mono-nodes" is seen as a concentration in a relatively small area of educational institutions – objects that provide a process of human lifelong learning, and it has been proved that such a concentration causes significant compaction of educational social mono-space in locations. objects of education. It has established that specialized educational mono-nodes in the material form began to be transformed into material-virtual socio-geographical objects with new characteristics. Practical meaning. The results of this study contribute to a deeper socio-geographical understanding of the processes of monodevelopment of specialized social nodes, their genesis, features of their course and provide an opportunity to model the long-term development of territorial social systems, to achieve expected results due to long-term transformation. They can be used for further study of monosystems of different hierarchical levels, as well as for the development of practical recommendations and programs for the development of individual monoterritories.

Метою даної роботи є дослідження спеціалізованих соціальних вузлів як домінантів соціального простору та результат спрямованості суспільно-географічних процесів до місць соціальної сили, їх «точковим» виразом в новітньому просторі регіону. Методика. В дослідженні використані загальнонаукові методи, зокрема аналіз, науковий синтез, аналітичний метод, методи порівняння та узагальнення. Наукова новизна. В статті величезна увага приділена спеціалізованим соціальним вузлам, які є домінантами соціального простору. Окреслено генезис перших соціальних вузлів як релігійних центрів для позначення святих місць в просторі, пошуку «центру світу» на конкретному ієрархічному рівні територіальної системи, упорядкування суспільно-географічних зв’язків та бачення світу стабільнішим. Розтлумачено дефініцію «спеціалізовані соціальні вузли» як моновузли, що формуються конкретним видом соціальноінфраструктурних об’єктів, котрий забезпечує один вид соціалізації чи виконує одну інфраструктурну послугу, забезпечуючи той чи інший вид соціалізації. Доведено, що соціальний простір можна розглядати на найбільш генералізованому рівні як соціальний монопростір під кутом взяття до уваги процесу соціалізації як генеруючої ознаки. Окреслено спеціалізовані освітні вузли як домінанти в спеціалізованому освітньому соціальному монопросторі, генералізованому на національному рівні, який формується всіма освітніми установами України. Розтлумачено дефініцію «спеціалізовані соціальні освітні вузли чи освітні моновузли» як концентрацію на відносно невеликій території освітніх закладів – об’єктів, які забезпечують процес освіти людини впродовж усього життя, причому доведено, що така концентрація обумовлює суттєве ущільнення освітнього соціального монопростору в місцях розташування об’єктів освіти. Встановлено, що спеціалізовані освітні моновузли у матеріальному вигляді почали трансформуватись у матеріально-віртуальні суспільногеографічні об’єкти з новими характеристиками. Практичне значення. Результати даного дослідження сприяють глибшому суспільно-географічному розумінню процесів монорозвитку спеціалізованих соціальних вузлів, їх генезису, особливостей їх протікання та дають можливість моделювати перспективний розвиток територіальних суспільних систем, досягати очікуваних результатів внаслідок довготривалої трансформації. Вони можуть бути використані для подальшого дослідження моносистем різного ієрархічного рівня, а також для розробки практичних рекомендацій та програм розвитку окремих монотериторій.
Монорозвиток спеціалізованих соціальних вузлів в структурі новітнього простору регіону
Keywords: територіальна система монорозвитку; монотериторія; спеціалізовані соціальні вузли; methodological territorial system of monodevelopment; monoterritory; specialized social nodes